Seismic protection of counterweight?rails in elevators in buildings. - Rildova, M. P. Singh (Earthquake engineering & structural dynamics.)
The counterweight in an elevator, being the heaviest component, can often overstress the guide rails during a strong earthquake. To reduce the in-plane counterweight response, the use of a part of the counterweight mass as a tuned mass damper in the passive and active modes is examined. The passive TMDs can reduce the stresses in the rails, but their performance can be significantly improved when they are used in the active mode. An actuator with saturation capacity less than 10% of the weight of the counterweight could reduce the critical stress response to as low a level as, or even lower than, the maximum response induced by the out-of-plane motion of the counterweight.